Tendencias emergentes y desafíos de las arquitecturas de software en la computación cuántica. Una revisión sistemática de la literatura - Orozco, Carlos Eduardo; Pardo Calvache, César Jesús (Revista Científica, 2024)
The rise of quantum computing has introduced a new paradigm in information processing, promising to surpass the limits of classical computing. However, the development of software architectures that can fully exploit this potential remains an ongoing field of study, filled with unprecedented challenges. This article presents the reported findings from a Systematic Literature Review on software architectures in the context of quantum computing, highlighting emerging trends and outlining the main challenges faced by this field. Through a formal and rigorous methodological approach, a total of 17 primary studies were identified and analyzed, revealing key patterns, design methodologies, and implementation strategies that are shaping the evolution of quantum software architectures. The results show a concentration of efforts on protocol standardization, quantum security, and scalability, along with growing concerns about interoperability with classical systems and the abstraction of quantum complexity for developers. This study not provides a critical consolidation of existing knowledge and lays the foundation for future research, identifying emerging areas and opportunities for disruptive innovations in the design and application of quantum software.